The Melanesian Way: Interpretation in the Context of Leadership and Consensus as the Approach to Solving Conflict - Tendy; Wirawan, Rendy; Yuniarti; Mulyani, Sari (Papua Journal of Diplomacy and International Relations, 2025)
This study examines the interpretation of the Melanesian Way in leadership and its role in conflict resolution within Melanesian communities. It aims to analyse how traditional leadership values, particularly the “Big Man” leadership model, contribute to social cohesion and dispute settlement. A literature review and narrative analysis were used to interpret the socio-political significance of Melanesian leadership structures. It argues that although the Melanesian Way refers to a complex system reflecting values and norms developed over thousands of years, it remains relevant today. The findings indicate that Melanesian leadership is deeply influenced by Christian values, shaping conflict resolution strategies that emphasize consensus, charisma, and social harmony. This research contributes to the broader understanding of indigenous governance by demonstrating how traditional leadership systems remain relevant in contemporary conflict management. By highlighting the effectiveness of culturally embedded governance mechanisms, this study offers insights into alternative models of conflict resolution beyond state-centric approaches. KEYWORDS Big Man; Consensus; Conflict Resolution; Melanesian Way